An Emerging Market: The Impact of User Selection on the Decision-Making Behavior of Mobile Medical Businesses in China - Xu, Xinglong; Wei, Jiajia; Zhou, Lulin; Antwi, Henry Asante (Frontiers in Psychology, 2022)
Background User selection is an important guarantee for the sustainable development of mobile medical businesses. Under the background of increasingly fierce competition, the decision-making behavior of mobile medical businesses will directly affect the choice of the behavior of users. Methods The study constructs the decision-making behavior model of mobile medical business based on the user choice and adds the role of people in government. It uses the game method to explore the relationship between the government, mobile medical business, and users. Finally, it makes an example analysis. Empirical research is conducted to demonstrate the influence of different parameter changes on the results. Results The results show that in the absence of government intervention, users’ choice of filtering information will create a bad environment for mobile medical businesses, and further will be reduced, and the expected utility of businesses will not be affected causing a reduction in expected utility of companies. Similarly, government regulations can effectively improve the mobile medical environment and enhance the expected utility of mobile medical companies. Conclusion The government needs to formulate relevant laws and regulations to ensure the orderly operation of the mobile medical market and strengthen government supervision. It is necessary to conduct publicity and education to protect the fundamental interests of users and businesses.